1992
DOI: 10.1111/j.1399-0004.1992.tb03257.x
|View full text |Cite
|
Sign up to set email alerts
|

The Wolf‐Hirschhorn syndrome in fetuses

Abstract: Wolf‐Hirschhorn syndrome (WHS) with partial deletion of the short arm of chromosome 4 has been exceptionally diagnosed in fetuses. We report prenatal diagnosis of five cases of monosomy 4p. The fetuses were karyotyped for severe intrauterine growth retardation (IUGR) diagnosed on routine ultrasound (US). In addition, cleft‐lip and palate and diaphragmatic hernia respectively were found in two cases. The quantity of amniotic fluid was normal in all cases. At autopsy, the fetuses showed the typical craniofacial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(29 citation statements)
references
References 19 publications
3
26
0
Order By: Relevance
“…7 In severe IUGR, karyotyping can reveal a 4p deletion and in these fetuses the only constant visceral anomaly on autopsy is major renal hypoplasia, as seen in the present case. 8 However, prenatal diagnosis of the 4p deletion can be difficult in the absence of major malformations and only borderline growth restriction with subtle facial anomalies (microretrognathia, short philtrum), as has been reported previously. 9 Moreover, deletions can be missed by traditional cytogenetics.…”
Section: Discussionmentioning
confidence: 91%
“…7 In severe IUGR, karyotyping can reveal a 4p deletion and in these fetuses the only constant visceral anomaly on autopsy is major renal hypoplasia, as seen in the present case. 8 However, prenatal diagnosis of the 4p deletion can be difficult in the absence of major malformations and only borderline growth restriction with subtle facial anomalies (microretrognathia, short philtrum), as has been reported previously. 9 Moreover, deletions can be missed by traditional cytogenetics.…”
Section: Discussionmentioning
confidence: 91%
“…Several studies have suggested that 15q24-26 and 8p23.1 are critical for normal development of the diaphragm since recurrent deletions within these regions were associated with CDH [33][34][35][39][40][41][42] . CDH has also been reported in several cases of monosomy 4p16pter associated with WolfHirschhorn syndrome [43][44][45] . Other candidate regions such as 1q41-q42, 6p22-p25, or 22q11 have also been described [23,36,38] .…”
mentioning
confidence: 95%
“…CDH is a severe birth defect characterized by defective formation of the diaphragm, lung hypoplasia and pulmonary hypertension. This has been previously described in 13 WHS patients [Lazjuk et al, 1980;Tachdjian et al, 1992;Kobori and Gregory, 1993;Bird et al, 1994;Howe et al, 1996;Del Campo and Delicado, 1997;Sergi et al, 1998;Tapper et al, 2002;van Dooren et al, 2004;Pober et al, 2005;Basgul et al, 2006;Casaccia et al, 2006;Battaglia et al, 2008]. Sporadic cases of complex heart defects in association with WHS have been reported [http://www.ncbi.nlm.nih.gov/bookshelf/ br.fcgi?book¼ gene&part¼whs].…”
Section: To the Editormentioning
confidence: 67%